Masked Extraction Machine, From Declared Conquest to Proclaimed Rescue - Kibavuidi Nsiangani; L Mawete; A Kiese (USK Journal of Political Science and Epistemology, 2019)
This paper tests a falsifiable claim about Western discourse on Africa from 1450 to 2019: rhetoric mutates – conquest, commerce, abolition, administration, development, “partnership” – while the underlying extraction architecture remains structurally stable. I propose a unifying concept, the Extraction–Inversion Architecture (EIA), defined by four elements: (i) sustained value transfer, (ii) coercive enforcement, (iii) narrative inversion that relocates causality and blame onto the targeted population, and (iv) continuity under changing moral brands. A minimal coding protocol separates External Pressure markers (credit, deadlines, enforcement) from Internal Attribution markers (kinship constraints, recoverability, explicit status distinctions). A pilot-coded corpus of 80 influential documents across four periods exhibits a crossover pattern: external-pressure language peaks in the commercial pivot (1650–1790) and is then erased or minimized in the missionary–administrative and development eras, replaced by heightened internal attribution. I integrate these results with ISM (Inversion & Sense-Making), PDI (Permission-Design Infrastructure), and the colonial Dark Tetrad to show how EIA structurally shapes institutions, capital flows, innovation, and Africa’s effective “license” to do business.
Discursive Continuity of a Single Extraction Architecture (1450–2019)
Keywords: Extraction–Inversion Architecture (EIA); Discursive Continuity; Narrative Inversion; Colonialism; Development Discourse; Atlantic Slave Trade; Pawnship; External Pressure Index (EPI); Internal Attribution Index (IAI); African Agency; Institutional Design; Dark Tetrad.